Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Les approches postcoloniales : apports pour un féminisme antiraciste - Benelli, Natalie; Delphy, Christine; Falquet, Jules; Hamel, Christelle; Hertz, Ellen; Roux, Patricia (Nouvelles Questions Féministes, 2006)
S’il existe une question féministe qui mérite approfondissement parce qu’elle est compliquée et recouvre des enjeux fondamentaux pour nos existences, c’est bien celle des imbrications structurelles entre l’oppression fondée sur le sexe et les oppressions fondées sur l’appartenance à une race, ethnie ou culture, regroupées ici sous l’appellation “racisme”. Nouvelles Questions Féministes revient ainsi, dans le présent numéro, sur la thématique amorcée dans le premier volume de cet ensemble de deux numéros consacrés au sexisme et au racisme. En effet, qu’il s’agisse de l’imposition du voile ou de son interdiction, de la prostitution, des mariages non consentis, des violences ou des discriminations sur les lieux de travail, l’oppression sexiste ne s’inscrit ni ne se lit dans le corps abstrait de “la femme” universelle et anhistorique, mais dans celui de femmes particulières et particularisées, dans un contexte social déterminé, caractérisé par d’autres rapports de domination.
https://www.cairn.info/revue-nouvelles-questions-feministes-2006-3-page-4.htm
Keywords: OFDIG; antiracisme; approches et analyses; cours; discours dominant; europe; fem1000; france; féminisme décolonial; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis